MORPHOLOGICAL RELATIONS OF BUKHARA OGHUZ DIALECTS WITH OTHER OGHUZ DIALECTS (ResearchJet Journal of Analysis and Inventions, 2021)
The article analyzes the morphology of Bukhara Oghuz dialects and their relationship to other Uzbek Oghuz dialects and the Turkmen language and its dialects.